Circannual Clock in Laelia speciosa (Orchidaceae) Through Dormancy vs. Germination Dynamics of Seeds Stored Under Controlled Conditions - Erandeni Durán-Mendoza; Martha Cornejo-Gallegos; Alejandro Martínez-Palacios; Martha Elena Pedraza-Santos; Nahum M. Sánchez-Vargas; Guadalupe Alejandra Valdovinos-Ramírez; Adelaida Stephany Hernández-Valencia; Juan Manuel Chavarrieta-Yáñez; Eloísa Vidal-Lezama; María del Carmen Mandujano-Sánchez (Plants, 2025)
This study aimed to determine the dynamics of dormancy using triphenyl tetrazolium chloride (TTC) and asymbiotic germination in Laelia speciosa (Kunth) Schltr. seeds stored for three years and one year at different temperatures. This is the first report of a circannual rhythm in L. speciosa seeds under controlled storage conditions. Two experiments were carried out: (a) with seeds from wild populations of L. speciosa collected at two different times and dehydrated to 4% relative humidity (RH) and stored for three years at 25 °C, 6 °C, −20 °C, and −80 °C, and (b) with seeds from six fruits stored in liquid nitrogen (LN2; −196 °C) at 25 °C for 12 months. The germination conditions were 25 ± 1 °C with 16 h of light (23 μmol m−2 s−1) and 8 h of darkness for both trials. Because they have a rudimentary embryo, orchids are attributed a morphological latency; however, the staining of the embryo with TTC (>92%) in all the evaluations carried out throughout a year and the decrease in asymbiotic germination in the intermediate evaluations record a circannual biological cycle or clock, under temperature and humidity control (4% RH).